Magnetic resonance imaging highlights the meningeal involvement in steroid responsive meningitis-arteritis and suggests the inflammation of the surrounding tissues (70 cases) - Remelli, Carlotta; Martello, Alba; Valentini, Alessia; Contiero, Barbara; Bernardini, Marco (Frontiers in Veterinary Science, 2022)
Introduction: Steroid-responsive meningitis-arteritis (SRMA) is an immune-mediated disorder of young dogs for which there is no definitive ante-mortem diagnostic test. Magnetic Resonance Imaging (MRI) can be used to explore other differentials and extensive reports about its usefulness in the diagnosis of SRMA are lacking. The aims of this study were to retrospectively investigate the characteristics of MRI studies of the cervical spine of dogs diagnosed with SRMA and to compare the diagnostic capability of MRI obtained with low-field and high-field units. Materials and Methods: This is a double center, retrospective case series. Databases were searched between 2008-2021 for dogs with a diagnosis of SRMA. Inclusion criteria were signalment, medical history, neurological examination, cerebrospinal fluid analysis suggestive of cervical SRMA and MRI of the cervical spine available for re-evaluation. Results: Seventy cases were selected. MRI abnormalities were found in 69 cases (98.6%). Enhancement of the meninges, nerve roots, synovium of the articular facets and paravertebral muscles was present in 61 (87.1%), 10 (14.3%), 34 (48,6%) and 34 (48,6%) cases respectively, when considering all MRI. In the low-field MRI, enhancement of these structures was present in 45 (90%), 4 (8%), 21 (42%) and 23 (46%) cases respectively. In the high-field MRI, enhancement of these structures was present in 16 (80%), 6 (30%), 13 (65%) and 11 (55%) cases respectively. Fat suppressed T1W images showed meningeal enhancement better than T1W images. When all the MRIs were considered, a significant increase in cell count of the cerebrospinal fluid was found between the three groups based on the meningeal MRI score (p=0.001). In cases with no meningeal enhancement but enhancement of synovium of the articular facets and/or muscles a significantly lower cerebrospinal fluid cell count was present (p=0.043), when considering all MRIs. Conclusions: The most frequent detection on cervical MRI of dogs affected by SRMA is meningeal enhancement, often accompanied by enhancement of the synovium of the articular facets and/or muscular enhancement. Both low-field and high-field MRI have good diagnostic capability but the latter enables a more thorough investigation thanks to specific sequences. MRI is useful as a complementary tool to cerebrospinal fluid analysis.